Pengembangan Rencana Pelaksanaan Pembelajaran Matematika Kurikulum 2013 Berbasis Lesson Study Pada Siswa Kelas VII SMP Kristen 2 Salatiga Tahun 2015/2016 - Risnawati, Shinta Devi; , Prof. Dr. Sutama, M.Pd (2016)
RPP math is very important, this is because the success of the learning process is determined by the RPP. Research and development aims aims to 1) analyze and describe the preparation of RPP mathematics curriculum in 2013 conducted by the teacher class VII Christian 2 Salatiga, 2) draw up the development of the RPP mathematics curriculum 2013-based lesson study in class VII Christian 2 Salatiga and 3) analyzing RPP eligibility math 2013 curriculum-based lesson study in class VII Christian 2 Salatiga developed. This type of research and development is the research and development (R & D) research design using evaluative research. Data collection techniques used were interviews, documentation and questionnaires. Data were analyzed using qualitative analysis methods flow and Delphi. Data validity is checked using triangulation and triangulation techniques. Results of research and development are 1) RPP mathematics curriculum in 2013 compiled by the Christian school teachers 2 Salatiga. Preparation of RPP attention and the principle constituent components RPP 2) development of RPP mathematics curriculum lesson study in 2013 based on class VII Christian 2 Salatiga. Development is done by developing components RPP RPP. 3) eligibility RPP 2013 mathematics curriculum lesson study in class VII Christian 2 Salatiga developed. RPP eligibility test using Delphi by experts earned an average of 76.6 with a decent category.